Dear Readers and Friends. - Bui, Phong (Brooklyn Rail)
The article offers miscellaneous information related to the contributions from Brooklyn. Two poems are presented including "You Sure Do Some Nice Things" by Bill Berkson and "When Lilacs Last in the Dooryard Bloom'd" by Walt Whitman. It presenst a quotation by Muhammad Ali. It offers informaiton on authors inlcuding Berkson, Whitman and Muhammad Ali.